Research supporting structure roof of the passenger terminal - Першаков, В.М.; Білик, А.О. (Proceedings of National Aviation University, 2008)
The article is devoted to the development of effective bearing building constructions: shells and suspending constructions. Basing on comparison analysis of two kinds of roof constructions (suspended constructions and shells) it is found the advantages and disadvantages of such constructions, and also, it is pointed out the peculiarities of its implementation for airport buildings.